Human Resource Development to Promote Innovative Entrepreneurship - Panittumrong, Watcharapong; Nirantawee, Sakchai; Whattananarong, Achara; Rasanon, Tharin (Journal of Humanities and Social Sciences, Rajapruk University, 2026)
This article on human resource development to promote innovative entrepreneurship aims to 1) study the characteristics and components of innovative entrepreneurship and 2) study human resource development approaches to promote innovative entrepreneurship. Key elements of innovative entrepreneurship include networking, effective communication, marketing strategy, motivation, innovation development, creativity, strategic management, team building, personal character, project management, future orientation, content knowledge and practical skills, leadership, financial savvy, negotiation, time management, and change management. Therefore, human resource development in business organizations should follow an approach encompassing training, education, organizational development, and career paths. This aims to enhance the entrepreneurial potential of subordinates, ultimately utilizing these capabilities to drive business operations more efficiently.